Mathematical Understanding and Student Self-Efficacy through Quantum Teaching Learning Models in Integral Materials - Desi Aria Mustika; Anwar Anwar; Hizir Hizir (Proceedings of AICS - Social Sciences, 2018)
Mathematical understanding and self-efficacy are things that must be considered in determining the success of student learning. However, based on preliminary studies at SMAN 1 Delima, those are still low. The purpose of this research was to know the significant improvement between mathematical comprehension and student self-efficacy facilitated by Quantum Teaching learning model and to see the correlation between mathematical understanding and student self-efficacy through Quantum Teaching learning model. This research was experimental research with quantitative approach. The study population was all students of class XI of SMAN 1 Delima. The sample of this research was randomly selected consisted of class XI IPA2 as the experimental class and class XI IPA3 as the control class. The instrument of this study was a mathematical understanding test and a student self-efficacy questionnaire that has been validated by three validators and has been tested in class XI IPA4. The results of the validity and reliability analysis of items on mathematical understanding and self-efficacy questionnaires were tested feasible. A t-test was used to find out the improvement of mathematical understanding and self-efficacy of students facilitated learning model Quantum Teaching. While to see the correlation between mathematical understanding and student self-efficacy, product moment Pearson correlation test was used. The study found that the improvement of students' mathematical understanding and self-efficacy facilitated by Quantum Teaching learning model was better than conventional learning. The correlation between mathematical comprehension and student self-efficacy facilitated by Quantum Teaching learning model was in a low category. Therefore, the quantum teaching model can be applied by teachers to improve students' understanding and self-efficacy on integral materials.Keywords: quantum teaching model, mathematical understanding, self-efficacy.